Sistem Pendukung Keputusan Penerimaan Dosen Tetap Menggunakan Fuzzy-Analytic Hierarchy Process - Made Agung Raharja; I.N Anom Cahyadi Putra (Jurnal Teknologi Informasi dan Komputer, 2015)
A decision is one problem facing almost every day, even every moment. This research will combine the capabilities of Logic Samar (Fuzzy Logic) with the Analytic Hierarchy Process (AHP-F). Use application with Fuzzy-AHP method is still rarely used or methods that are new in the  making  of  a  decision  support  system  for  Fuzzy  AHP  makes  the  problem  a  broad  and unstructured become a model that is flexible and easy to understand.Decision Support System Acceptance Lecturers Using Fuzzy-Analytic Hierarchy Process (AHP-F). (Case Study: University of Dhyana Pura Bali), it can be concluded as follows: Knowing what  the  user  needs  in  a  decision  support  system  acceptance  tenured  faculty.  The  screening decision support system of filing of lecturers using fuzzy AHP method at the University of Dhyana Pura consists of several stages. First, create the structure. Furthermore, determining the value of fuzzy  synthesis  (Si)  priorities,  determine  the  value  of  the  vector  (V)  and  the  ordinate  value defuzzification (d '). Calculating normalized values fuzzy weight vector (W) equal to the weight of global priorities. With Fuzzy AHP, form a decision support system that can select prospective teachers, and determine who deserves and is entitled to be accepted as a lecturer at the University of Dhyana Pura. Keywords: DSS, Fuzzy-Analytic Hierarchy Process (F-AHP)